FROM ECONOMIC ASSET TO SELF-ACTUALIZATION PROJECT: A HISTORICAL ANALYSIS OF THE SHIFTING SYMBOLIC VALUES ​​OF CHILDREN AND THE EMERGENCE OF THE CHILDFREE OPTION - Fikri, Khirpal; Wahyuni, Syarli (Academic Solution Publisher, 2025)
This study aims to analyze the historical transformation of children's value from economic assets to emotional symbols and self-actualization projects in modern society and its relationship to the emergence of the childfree phenomenon. Using a historical qualitative approach through a library study of classical and contemporary literature, this study traces the changes in children's values ​​within social, economic, and cultural contexts. The results show that the shift in children's values ​​occurs in layers: from a productive function in pre-modern times, to a symbol of affection in the modern era, to the center of emotional projects that require great sacrifice in post-industrial society. The ideology of intensive parenting positions children as emotionally